SO060MONOCYTE-TO-LYMPHOCYTE RATIO, AN INDEPENDENT RISK FACTOR OF SURVIVAL IN HEMODIALYSIS PATIENTS: RESULTS FROM THE INTERNATIONAL MONDO CONSORTIUM. (6th June 2020) - Bright, Rupert; Ye, Xiaoling; Woollard, Kevin; Pusey, Charles Dickson; Kotanko, Peter; Duncan, Neill
Abstract: Background and Aims: Patients with end-stage kidney disease have a high prevalence of chronic inflammation and a higher risk of death. Previous work by our group has indicated a positive relationship between neutrophil counts and neutrophil-to-lymphocyte ratio (NLR) and mortality in a large and ethnically diverse dialysis population. Monocytes also have a crucial inflammatory role, but there has been limited study to date, an association between monocyte-to-lymphocyte ration (MLR) was reported in a small Chinese haemodialysis cohort. The aim of this analysis was to study the independent relationship between MLR and all-cause mortality in a large and ethnically diverse haemodialysis population. Method: Four cohorts were described by phases of haemodialysis exposure: 1) acute phase cohort- first 90 days on HD as the baseline period with the subsequent 9 months as the follow-up period, 2) early-stable phase cohort- 91 days to the end of 1 st year as the baseline followed with 1 year's follow-up period, 3) mid-stable phase cohort- 2 nd year as the baseline and the following 1 year as the follow-up, and 4) late-stable phase cohort- 3 rd year as the baseline followed by a 7 year follow-up period. All-cause mortality was recorded during the 4 phases. Kaplan-Meier (KM) curves were applied to explore the association between MLR quartiles with mortality in the 4 cohorts. Cox proportional hazards models with spline terms (adjusted for age, gender, race, body mass index, diabetic (DM) and congestive heart failure (CHF)) were applied to explore the association between MLR levels and all-cause mortality in the cohorts. Results: A total of 20, 848 patients were included in acute phase cohort; 19, 575 in the early-stable phase cohort, 16, 515 patients in the mid-stable cohort, and 13, 708 patients in the late-stable phase cohort. Notably, patients with higher baseline MLR by quartile tended to be older, male and with a higher percentage of DM and CHF as comorbidities. Lower lymphocyte count and higher neutrophil count, NLR, CRP were associated with higher MLR quartile (Table 1), consistent with the observed association with other markers of inflammation and malnutrition: lower albumin, phosphate and higher ferritin. Adjusted all-cause mortality was observed to be higher in patients with higher MLR quartile both in the KM and spline analyses (Figure 1 a & b) in all phase cohorts (data not shown). Conclusion: There is a positive relationship between higher levels of MLR and adjusted all-cause mortality across all phase cohorts, including long-term follow-up in this large and ethnically diverse haemodialysis population. Higher levels of MLR are seen in patients with DM and CHF and are consistently observed with other markers of inflammation and malnutrition. This work supports the findings made previously in a more a restricted cohort and warrants further mechanistic investigation.